Espacial and temporary analysis of water stress index in the river Quindío basin (Revista de Investigaciones Universidad del Quindío, 2011)
The stress index quantifies the water that a region produces. Also, it helps to infer how much water from that volume is needed; and it represents the ratio between the water demand and supply. In Quindío, the water supply has not been properly settled and the existing streamflows have not been established into the rules and regulations. This situation does not allow seeing the reality to identify the quantity of water available for different uses. The demand is concentrated in urban areas, but the water administration from the companies that manage this service is not efficient enough. The non suitable social manage is evident, such as the low capacity of flow stream regulation due to the changes in the soil uses and the lack of source protection in the higher elevation areas at basins. The research in Corporación Autónoma Regional of Quindío has quantified the water supply in the control flow points at each catchment through lumped models. This makes it necessary to study a distributed model because there are some reaches affected by the little flow quantity in unstressed basins.
Keywords: Hydrology; Water Supply; Water Demand